Globalization, Green Economy and Environmental Challenges: State of the Art Review for Practical Implications - Zhang, Lin; Xu, Meng; Chen, Huangxin; Li, Yuexinyi; Chen, Shuiguang (Frontiers in Environmental Science, 2022)
Globalization has significantly influenced the economy, ecology, and society during the previous decade. Meanwhile, the green economy has emerged as a critical policy framework for growth and development in developed and developing countries. The current study is an attempt to provide a detailed review on globalization, green economy, and climate challenges to draw some implications. There are disagreements between competing green economic discourses and a variety of definitions, all of which have problems. Recognizing the environmental effects of natural resource depletion and the economic benefits of environmental management are common examples of green economy operationalization. The new study also examines climate change's impact on the green economy and infrastructure development. The study further considers the role of economic structure to mitigate environmental issues, increase production efficiency, enhance green economy and environmentally friendly technologies. The present study concluded that working toward a green economy helps reduce poverty in the four ways indicated in this study. It also shed a brief light to improves poor people's access to a healthy and safe environment while increasing human security by preventing or resolving conflicts over land, food, water, and other natural resources.